Extreme Programming Method for Efficient and User-Friendly Web-Based Photo Studio Reservations: Pilvi Project Case - Gherika Gerungan; Winsy Weku; Eric Alfonsius (Jurnal Informatika dan Rekayasa Perangkat Lunak, 2026)
The development of information technology has accelerated the digitalization of services across various sectors, including the photography industry. Pilvi Project is a photo studio that offers photography services for various needs, such as graduation photos, ID photos, and more. However, the current reservation process, which is still carried out manually via WhatsApp, presents several challenges, including scheduling conflicts and limited access to service information for users. This study aims to design and develop a web-based photo studio reservation system using the Extreme Programming (XP) methodology. XP was chosen for its iterative and flexible approach, which allows for rapid adaptation to user needs. The system includes key features such as user registration and login, studio reservations based on availability, service package selection, and admin-controlled data management. The result of this study is a structured and organized photo studio reservation website capable of efficiently managing bookings. Based on black-box testing, all system features functioned as intended. Questionnaire results indicated positive user responses, highlighting the system's ease of use and overall user experience. An evaluation by the Pilvi Project team confirmed that the system successfully met their requirements.